KHIYAR AL-RU’YAH ON ONLINE TRANSACTIONS; AN ANALYSIS CONTEMPORARY MUAMALAH MALIYAH - Syaichoni, Ahmad; Setiawan, Didik (An-Nisbah: Jurnal Ekonomi Syariah, 2022)
This research is backed by the phenomenon of online transactions conducted by the people of the modern era. Online transactions emerge due to the development of technology and information that can help human beings buy and sell transactions efficiently. However, online transactions pose an individual problem as fraud. Islam governs that every transaction should prioritize a mutual attitude so that no party is harmed. Islam guarantees that all forms of transactions must be free from anything that could harm either party. This article will discuss Islam's concept to protect the parties in the transaction, especially in online transactions. This research is a research library with a normative juridical approach. The data analysis used is content analysis and critic analysis. This research can conclude that al-ru'yah may be applied to online transactions as a form of collateral protection provided to the consumer. Khiyar al-ru'yah attempts to ensure that the consumer knows the goods are transacted so that no party is harmed.